2005
DOI: 10.1016/j.cellbi.2004.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular chaperone, HSP60, and cytochrome P450 2E1 co‐expression in dilated cardiomyopathy

Abstract: Physiological stresses (heat, hemodynamics, genetic mutations, oxidative injury and myocardial ischemia) produce pathological states in which protein damage and misfolded protein structures are a common denominator. The specialized proteins family of antistress proteins - molecular chaperons (HSPs) - are responsible for correct protein folding, dissociating protein aggregates and transport of newly synthesized polypeptides to the target organelles for final packaging, degradation or repair. They are inducible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 23 publications
4
30
0
Order By: Relevance
“…[47][48][49][50] Thus, it is possible that hypoxemia in a state of cardiomyopathy triggers the formation of acetone, which then induces CYP2E1 to enhance the metabolism of endogenous ketones to meet the energy demand of the heart. The expression of CYP2E1 increases significantly in heart diseases, [13][14][15][16][17] and here we found that the expression of CYP2E1 also increased in ADR-induced DCM heart and Lmna E82K DCM mice ( Figure 1A and 1B). The previous reports and our results suggest that the upregulation of CYP2E1 might be an important molecular event to meet the energy demand in diseased hearts.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…[47][48][49][50] Thus, it is possible that hypoxemia in a state of cardiomyopathy triggers the formation of acetone, which then induces CYP2E1 to enhance the metabolism of endogenous ketones to meet the energy demand of the heart. The expression of CYP2E1 increases significantly in heart diseases, [13][14][15][16][17] and here we found that the expression of CYP2E1 also increased in ADR-induced DCM heart and Lmna E82K DCM mice ( Figure 1A and 1B). The previous reports and our results suggest that the upregulation of CYP2E1 might be an important molecular event to meet the energy demand in diseased hearts.…”
Section: Discussionsupporting
confidence: 48%
“…[10][11][12] The expression level of CYP2E1 increases significantly in heart tissues in humans under ischemia; mice, rats, and dogs with dilated cardiomyopathy (DCM); and spontaneously hypertensive rats. [13][14][15][16][17][18] The overexpression of CYP2E1 is associated with several cellular markers of oxidative stress, as well as with decreased viability as a result of both necrosis and apoptosis. [19][20][21][22] Oxidative stress and apoptosis in myocytes play important roles in the pathogenesis of cardiovascular diseases, such as ischemic heart disease, atherosclerosis, cardiomyopathy, and heart failure.…”
mentioning
confidence: 99%
“…Cyp2e1 activity may be an important mediator of oxidative stress response in the heart. Cyp2e1 activity is elevated in ischemic hearts and in hearts with dilated cardiomyopathy (Sidorik et al 2005). Lipid peroxidation in cardiomyocytes treated with acetaldehyde (a component of ambient particles) is reduced by the Cyp2e1 inhibitor, diallyl sulfide (Aberle and Ren 2003).…”
Section: Discussionmentioning
confidence: 99%
“…ed cardiomyopathy than that in healthy human hearts (Sidorik et al, 2005). The physiological importance of these enzyme emerge from their ability to metabolize arachidonic acid to various cardiotoxic metabolites, particularly hydroxyeicosatetraenoic acid (HETEs) (Elbekai and El-Kadi, 2006).…”
Section: Resultsmentioning
confidence: 99%